2021
DOI: 10.1002/adom.202100636
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Near‐Infrared Perovskite Light‐Emitting Devices by Introducing Choline Chloride Layer

Abstract: The existing interface defect states between perovskite and the transport layer is one of the dominant reasons to limit the performance of near‐infrared (NIR) perovskite light‐emitting devices (PeLEDs). Herein, a quaternary ammonium halide choline chloride layer is introduced to improve the wettability of the hole transport layer (HTL) and passivate defect states. As a consequence, the performance of the NIR PeLEDs is obviously enhanced. A maximum output power density of 4.7 mW cm−2 has been achieved by optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…The choline chloride was spin‐coated onto the HTL at 4000 rpm for 60 s with annealing at 100 °C for 10 min to form a passivation layer. [ 8 ] The perovskite precursor was then deposited on choline chloride with two‐step spin‐coating procedures in air‐ambient. The first step was 500 rpm for 10 s with an acceleration rate of 200 rpm/s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choline chloride was spin‐coated onto the HTL at 4000 rpm for 60 s with annealing at 100 °C for 10 min to form a passivation layer. [ 8 ] The perovskite precursor was then deposited on choline chloride with two‐step spin‐coating procedures in air‐ambient. The first step was 500 rpm for 10 s with an acceleration rate of 200 rpm/s.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance the Si-based PeLEDs, energy level control, band matching, as well as interface passivation between perovskite and silicon are still problems that need to be solved.In previous works, [6,7] we first fabricated Si-based PeLEDs and enhanced the EQE from less than 0.1% to 0.91% via energy level control. Then, we passivated the interface defects in the device [8] and adjusted the device structure to increase device efficiency. [9] Further, the surface of the perovskite was modified by PMMA anti-solvent doping, so that the device can operate normally in a high humidity atmosphere, and an EQE of 7.5% is obtained.…”
mentioning
confidence: 99%
“…11g). 26 Choline chloride was used as passivation layer to improve the EL intensity of devices. The LEDs with 0.5 mg ml À1 choline chloride achieved higher EL intensity than other devices.…”
Section: Si-based Perovskite Light Emitting Diodesmentioning
confidence: 99%
“…25 Furthermore, Xu et al used a similar design to fabricate Si-based MAPbI 3 LEDs with near-infrared (787 nm) emission. 26 Fig. 1d shows the schematic illustration of an optically pumped perovskite/Si laser as reported e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, AC-driven EL devices have obvious advantages in some important aspects, including stable operation and color tunable integrated devices. For example, Xu et al demonstrated the perovskite quantum dot LEDs in different drive modes (DC and AC) . The operating stability of AC-driven EL devices was 4× longer than that of DC-driven devices at a high current density of 300 mA cm –2 , which was ascribed to the suppressed heating and reduced charge accumulation during operation.…”
Section: Introductionmentioning
confidence: 99%